The Organizational Innovation System: A systemic framework for radical innovation at the organizational level. (June 2016) - Van Lancker, Jonas; Mondelaers, Koen; Wauters, Erwin; Van Huylenbroeck, Guido
Abstract: Most research on innovation management at the organizational level has typically been focused on one specific innovation project phase or innovation management concept. This has resulted in many valuable insights, though scattered in different (innovation) research fields and studies. With the development of the Organizational Innovation System (OIS), we bring together important insights from the Innovation Systems, Open Innovation and other related fields into a guiding concept useful for both innovation managers developing (radical) innovations and innovation scholars. In this paper, we define the OIS and its key structural components, and discuss the identified functions and categories of potential imperfections. With the OIS, we provide a holistic, hands-on concept currently lacking in the open innovation approach. From the conceptualization, a framework for analysis is put forward which provides structure to the study of ongoing and finished innovation processes. Additionally, the development of the OIS is a first step in the development of a currently underdeveloped micro-level within the innovation systems perspective. The insights in OISs and the future insights derived from analytical efforts, will not only be beneficial for the performance of innovating organizations and organizational innovation systems but also for the performance of the higher, interconnected system levels. Highlights: Organizational Innovation System: micro-level to innovation systems perspective. Guiding concept for innovation managers in radical innovation development processes. Main components, supporting functions, potential system imperfections are developed. Framework for analysis is developed to study ongoing and finished projects. Resulting insights and best practices benefit higher interconnected system levels.